Low levels of caspase-3 predict favourable response to 5FU-based chemotherapy in advanced colorectal cancer: caspase-3 inhibition as a therapeutic approach - Flanagan, Lorna; Meyer, M.; Fay, J.; Curry, S.; Bacon, O.; Duessmann, H.; John, K.; Boland, K. C.; McNamara, D. A.; Kay, E. W.; Bantel, H.; Schulze-Bergkamen, Henning; et al. (Cell death & disease, 2016)
Colorectal cancer (CRC) is one of the most common cancers in the Western world. 5-Fluorouracil (5FU)-based chemotherapy (CT) remains the mainstay treatment of CRC in the advanced setting, and activates executioner caspases in target cells. Executioner caspases are key proteins involved in cell disassembly during apoptosis. Activation of executioner caspases also has a role in tissue regeneration and repopulation by stimulating signal transduction and cell proliferation in neighbouring, non-apoptotic cells as reported recently. Tissue microarrays (TMAs) consisting of tumour tissue from 93 stage II and III colon cancer patients were analysed by immunohistochemistry. Surprisingly, patients with low levels of active Caspase-3 had an increased disease-free survival time. This was particularly pronounced in patients who received 5FU-based adjuvant CT. In line with this observation, lower serum levels of active Caspase-3 were found in patients with metastasised CRC who revealed stable disease or tumour regression compared with those with disease progression. The role of Caspase-3 in treatment responses was explored further in primary human tumour explant cultures from fresh patient tumour tissue. Exposure of explant cultures to 5FU-based CT increased the percentage of cells positive for active Caspase-3 and Terminal Deoxynucleotidyl Transferase dUTP Nick end Labelling (TUNEL), but also the expression of regeneration and proliferation markers β-Catenin and Ki-67, as well as cyclooxygenase-2 (COX-2). Of note, selective inhibition of Caspase-3 with Ac-DNLD-CHO, a selective, reversible inhibitor of Caspase-3, significantly reduced the expression of proliferation markers as well as COX-2. Inhibition of COX-2 with aspirin or celecoxib did not affect Caspase-3 levels but also reduced Ki-67 and β-Catenin levels, suggesting that Caspase-3 acted via COX-2 to stimulate cell proliferation and tissue regeneration. This indicates that low levels of active Caspase-3 may represent a new predictor of CT responsiveness, and inhibition of Caspase-3, or antagonising downstream effectors of Caspase-3 paracrine signalling, such as COX-2 may improve patient outcomes following CT in advanced CRC.
Gesehen am 02.06.2020